The Strategy of the Indonesian Army in Logistics and Material Support to Enhance Border Security Operations in the Indonesia–Papua New Guinea Border Area - Keyko Nasya; Mitro Prihantono; Marsono (Journal of Education Religion Humanities and Multidiciplinary, 2026)
The border area between the Republic of Indonesia and Papua New Guinea (RI–PNG) is characterized by difficult geographical conditions, limited infrastructure, and a high level of security vulnerability, which require optimal logistics and material support to sustain security operations. However, in practice, the provision of logistics and material support by the Indonesian Army still faces various challenges, particularly in planning, management, and optimization. These conditions have the potential to affect the continuity and effectiveness of operational tasks in border areas. This study aims to analyze the forms and strategies of logistics and material support implemented by the Indonesian Army in supporting border security operations in the RI–PNG region. This research employs a descriptive qualitative method with data collected through interviews, field observations, and document analysis. Data analysis is conducted using the analytical framework of defense science theory, the Ends–Ways–Means strategic theory, and military logistics management theory. The results indicate that logistics and material support includes the provision of essential supplies, phased distribution mechanisms, and adaptive utilization at the unit level. Support strategies are implemented through operation-based planning, administrative-operational management, and field-initiative-based optimization. However, the logistics system remains conventional and has not been fully integrated. This study concludes that strengthening region-based planning, integrating logistics information systems, enhancing personnel competence, improving distribution infrastructure, and conducting continuous evaluations are necessary. These recommendations are expected to improve the sustainability and effectiveness of logistics and material support in border security operations in the RI–PNG area.